PEMBERDAYAAN PETANI MISKIN DI PEDESAAN: ANALISIS PENGALAMAN PROGRAM SLT DAN IDT (EMPOWERING POOR FARMER IN VILLAGES: ANALYSIS OF EXPERIENCE OF SLT AND IDT PROGRAMME) - Widiputranti, Christine Sri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
There are two events that almost similar, first, economy crisis in 2005 because increasing oil price almost 100 percent, second, economy crisis in 1997 because monetary situation. In 2005, government carried out SLT programme for solving poverty, and in 1997 government carried out IDT programme. SLT programme was not followed by empowering poor farmer, but IDT programme was followed by empowering poor farmer. IDT programme gave capital for business for instance livestock, and gave livestock extension and guidance. The result of empowering poor farmer were, there were increasing income level and saving ability of poor farmer.